PARTISIPASI MASYARAKAT DALAM MENDUKUNG PANTAI TANUSANG DESA GESER SEBAGAI KAWASAN EKOWISATA - Papilaya, Renoldy Lamberthy; Rumagoran, Yusril; Botanri, Adnan A. A. (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Community participation is the voluntary involvement of the community in achieving common goals. There are several issues in the development of Tanusang Beach in Geser Village as a destination that does not yet prioritize the principles of ecotourism, such as the lack of community involvement in management and the lack of educational principles. This study aims to identify the forms and levels of community participation in supporting Tanusang Beach in Geser Village, as well as to determine the direction of community-based ecotourism development in the area. The mixed method approach was used to identify the forms and levels of community participation through questionnaire distribution, Likert scale calculations, and interviews to determine the direction of development. The results of the study showed that the forms and levels of community participation were quite participatory, with 65.9% participating intellectually and 61.6% participating in the form of labor contributions. Furthermore, from the hierarchical analysis of stakeholder participation, the level of community participation in Kilwaru and Kampung Baru hamlets is still low because the majority of the community is at the level of tokenism, with the highest scores being at the informing level (73.7%) and consultation level (68.9%). Community participation is needed in developing ecotourism areas because it can drive other ecotourism principles such as economic principles, educational principles, and conservation principles. Community participation is also an important part of ecotourism development and can increase productivity so that the surrounding community can enjoy the economic benefits.